Comparative biomechanical study of using decellularized human adipose tissues for post-mastectomy and post-lumpectomy breast reconstruction. (April 2016) - Haddad, Seyyed M.H.; Omidi, Ehsan; Flynn, Lauren E.; Samani, Abbas
Abstract: Developing suitable biomaterials for post-mastectomy or post-lumpectomy breast reconstruction is highly important. This study is aimed at evaluating biomechanical suitability of decellularized adipose tissue (DAT) for this purpose. The study involves computational experiments for evaluating deformation of the breast reconstructed using DAT under loading conditions pertaining to two common body position changes of prone-to-supine and prone-to-upright. This was conducted using nonlinear finite element models where the breast geometry was obtained from MRI image of a female breast. The experiments were performed using DAT sourced from various adipose tissue depots in comparison to natural adipose tissue. Data obtained from the conducted experiments showed no contour defects with various DAT materials for simulated post-mastectomy or post-lumpectomy breast reconstruction under the loading conditions. They also demonstrated that a breast reconstructed using DAT derived from the breast or subcutaneous abdominal depots exhibit significantly closer deformation, both qualitatively and quantitatively, to that of a normal breast under the same loading conditions. Similarity of DAT deformation to that of natural breast tissue in post-surgery breast reconstruction was assessed using nonlinear finite element analysis. Our results provide evidence that DAT derived from subcutaneous abdominal and breast depots yield more analogous deformation pattern to the natural tissue in post-mastectomy breast reconstruction applications. This is quite encouraging, as breast and subcutaneous adipose tissue can be readily obtained in large quantities from breast or abdominal lipo-reduction surgery procedures. Furthermore, in post-lumpectomy cases all DAT samples used in this research showed similar deformation, and thus are suitable as breast tissue substituents.